2013
DOI: 10.1159/000353905
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Lipopolysaccharide Inhibits Influenza Virus Infection of Human Macrophages and the Consequent Induction of CD8+ T Cell Immunity

Abstract: It is well established that infection with influenza A virus (IAV) facilitates secondary bacterial disease. However, there is a growing body of evidence that the microbial context in which IAV infection occurs can affect both innate and adaptive responses to the virus. To date, these studies have been restricted to murine models of disease and the relevance of these findings in primary human cells remains to be elucidated. Here, we show that pre-stimulation of primary human monocyte-derived macrophages (MDMs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
0
16
1
1
Order By: Relevance
“…These interactions can be either direct 118,119 or indirect through the host immune system. For example, infection by influenza virus was shown to be less efficient following immune priming by lipopoly saccharide (LPS)mediated TLR4 activation of innate immune cells 120,121 .…”
Section: T Helper 17 Cellsmentioning
confidence: 99%
“…These interactions can be either direct 118,119 or indirect through the host immune system. For example, infection by influenza virus was shown to be less efficient following immune priming by lipopoly saccharide (LPS)mediated TLR4 activation of innate immune cells 120,121 .…”
Section: T Helper 17 Cellsmentioning
confidence: 99%
“…Bacterial lipopolysaccharide (LPS) has been shown to protect mice against HPAI virus infection through toll‐like receptor stimulation and might explain the relative mildness of the illness seen in our rural population, as none of them were subsequently hospitalized or died. Bacterial LPS has also been shown to inhibit the induction of CD8+ T‐cell immunity by influenza virus infection . One possibility is that high levels of bacterial LPS in the environment, by suppressing T‐cell responses, increase the ratio of asymptomatic to symptomatic influenza virus infections, leading to our observed higher rates.…”
Section: Discussionmentioning
confidence: 94%
“…Bacterial LPS has also been shown to inhibit the induction of CD8+ Tcell immunity by influenza virus infection. 37 One possibility is that high levels of bacterial LPS in the environment, by suppressing T-cell responses, increase the ratio of asymptomatic to symptomatic influenza virus infections, leading to our observed higher rates. Our observation that the relationship is dose-dependent supports this hypothesis.…”
Section: Discussionmentioning
confidence: 95%
“…The Lipopolysacharrides (LPS) that is present at the surface of Gram-negative bacteria [76] plays probably a role in the acquisition or severity of viral respiratory infections as an in vitro model has demonstrated that pre-stimulation of primary human monocyte-derived macrophages (MDMs) with LPS could reduce the infectivity of influenza A [77]. It has been also demonstrated that the adequacy of the antiviral immune response could be driven by LPS signaling.…”
Section: Mechanisms Possibly Involvedmentioning
confidence: 99%